The effect of Toxoplasma gondii infection in women on some biochemical and hormonal parameters in Duhok province, Iraq - Mikaeel, Farhad B. (International Journal of Research in Medical Sciences, 2020)
Background: Toxoplasma gondii is protozoal parasite that cause Toxoplasmosis, which is an important protozoal disease that infect more around billion people globally. Toxoplasmosis transmitted by two way in human; the horizontal transmission by accidental and ingestion of oocysts of Toxoplasma gondii through contaminated water or food, and the second rout is vertical transmission by placenta from mother to the baby. The aim of the current study was to detect the effect of toxoplasmosis on kidney function, liver function enzymes and gonadotropin hormones like follicle-stimulating hormone (FSH) and Luteinizing hormone (LH). Methods: A total of 101 (71 samples and 30 controls) of blood samples were collected from women, which were tested for seropositivity against anti-toxoplasma antibodies like immunoglobulin G (IgG), immunoglobulin M (IgM) by ELISA. After that the biochemical test (alanine aminotransferase-ALT, Aspartate transaminase-AST, Alkaline phosphatase-ALP, Urea and Creatinine) and hormonal assay (LH and FSH) and achieved for all samples. Results: Results revealed a slight increase in the level of both urea and creatinine in infected women compared with the control group. A Pearson’s Coefficient Correlation test was used to examine the positive correlations between ALT and Anaplastic lymphoma kinase (ALK), LH and FSH at p value (<0.001 for both). Preliminary studies indicate that the level of LH and FSH in infected women is lower compared to control healthy group. Finally, current study indicated that toxoplasmosis is effect on the levels of studied biochemical and hormonal parameters. Conclusions: Current study shows a significant increase in the levels of biochemical and hormonal parameters in women infected with toxoplasmosis.